Perceptions of telemedicine at a pediatric otolaryngology-head and neck surgery program. Issue 4 (10th November 2022) - Gwilt, Claire; Metzger, Gregory; Jatana, Kris; Bourgeois, Tran; Walz, Patrick
Abstract : Objective: With few studies investigating the effectiveness of telemedicine (TM) in pediatric otolaryngology (ear, nose, and throat; ENT), its role in clinical practice is unclear. The objective of this study was to investigate provider perspectives regarding utility of TM in pediatric ENT practice. Methods: A survey gauging the relative merits of TM visits for common pediatric ENT chief complaints and postoperative visits was distributed to all pediatric ENT providers at a tertiary care, free-standing children's hospital. Respondents were asked to assess the effectiveness of TM visits compared with in-person visits for completing the following tasks: history collection, physical examination, medical decision-making, and patient counseling. Results: Providers rated TM visits as less useful than in-person visits for completing the most predefined tasks but did identify advantages in history taking via TM for the majority of complaints. Compared with providers with ≥10 years of experience, those with <10 years of experience found TM to be more effective than the in-person appointment for making clinical decisions for patients presenting with recurrent/chronic pharyngitis, neck masses, and stridor/noisy breathing. Opinions regarding the utility of TM for postoperative visits were mixed, with adenoidectomy, tonsillectomy and superficial procedures being most frequently deemed appropriate for TM. Conclusions: The introduction of TM to pediatric ENT faces limitations in detailed examination of areas not accessible without specialized instrumentation. Due to its strength in history taking, results suggest an asynchronous, 'store and forward' encounter followed by an in-person physical examination to confirm the diagnosis and treatment plan could be beneficial.